Modes and Frequencies of Colonization and its Relation to Extinctions, Habitat and Seasonality in the Social Spider Anelosimus Eximius in the Amazon (Araneidae: Theridiidae) - Venticinque, Eduardo M. [UNESP]; Fowler, Harold G. [UNESP]; Silva, Carlos A. [UNESP] (Wiley, 1993)
Numbers of colonizations and extinctions of incipient colonies of the social spider Anelosimus eximius were greater at the edges of Amazonian forest than in continuous forest. The frequency of colony foundations by sociotomy, or groups, was higher in continuous forests than forest edges. Mean colony life spans for interior forest colonies were significantly longer, as well as colony life spans of colonies founded by sociotomy when compared with solitary foundations. Colony extinctions did not demonstrate monthly variations, although colony foundations showed significant differences, and were negatively correlated with monthly precipitation. We conclude that modes of colony foundation are habitat and seasonally dependent, related to the probability of survival. © 1993, Hindawi Publishing Corporation. All rights reserved.
Keywords: Anelosimus; colonization; colony; dispersal; extinction; sociotomy; spider; survivorship